Maternal Mortality: A Global Tragedy A GIS screening approach to the Problem - Alnoury, Ahmed Hamad (Gezira Journal of Health Sciences; Vol 1 No 1 (2004), 2004)
The Geographical Information System ( GIS) is a new approach for looking at global morbidity and mortality. The GIS is used to produce simple and self explaining maps showing malaria transmission zones and maternal mortality ratios world- wide . Then the same system is used for Sudan taking MMR, expected deliveries and live time risk as indicators. The presentation also includes strategies for maternal morality reduction in the Sudan based on two international approaches. The first is the Millennium Development Goal MDG, 2000) and the second is the international Conference for Population and Development ( ICPD, 1994). The strategy advocates two scenarios for the reduction of maternal mortality in the Sudan. The first is to reduce MMR from 550 per 100000 live births  to 138 by the year 2015 based on DHS , 1989 information; and the second is to reduce MMR from 509 per 100000 live births  to 127 by the year 2015 . based on SMS, 1999 information.